Hydrothermal Treatment, Sawdust, Corn Cob, Mixture, Solid Fuel - Cyrilla Oktaviananda; Agus Prasetya (Agrotechnology Innovation (Agrinova), 2019)
Hydrothermal treatment is a thermochemical process that converts biomass into a coal-like material called hydrochar by applying elevated temperature to biomass in suspensions with water under saturated pressure for a certain time. With this conversion process, easy to handle fuel with well-deﬁned properties can be created from biomass residues, even with high moisture content. Biomass is one of the renewable energy resources in Indonesia which has abundant resources potential. In this research, the eﬀect of corn cob-sawdust mixture w/w (100%:0%), (75%:25%), (50%:50%), (25%:75%) and (0%:100%) at initial pressure 1.0 MPa to hydrothermal treatment of biomass were examined. All samples were then characterized in terms of yield, proximate analysis, caloriﬁc value, and changes in functional groups by FTIR. Approximately 47-68% of origin material was recovered as a hydro-char. The gross caloriﬁc value ranged from 5160-5402 cal/gram. Hydrothermal treatment of sawdust and corncobs mixture with ratio 100% sawdust produced solid with higher heating value of 5402 cal/gram.